Chiroplasmon-active optical fiber probe for environment chirality estimation; Sensors and Actuators B: Chemical; Vol. 343 - Miliutina E. V. Elena Vadimovna; Zadny Ja. Jaroslav; Guselnikova O. A. Olga Andreevna; Storch Ja. Jan; Walaska H. Hana; Kushnarenko A. Anna; Burtsev V. Vasilii; Svorcik V. Vaclav; Lyutakov O. E. Oleksy Evgenjevich (2021, 2021)
Title screen